ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER PEDULI LINGKUNGAN MELALUI PEMBUATAN TOPENG DAUR ULANG PADA SISWA KELAS 5 DI SEKOLAH DASAR - Alya Fahrunnisa; Yulianti; Didik Iswahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of environmental character education through a recycled mask-making activity among fifth-grade students at Elementary School. The research employed a descriptive qualitative approach with data collected through observation, interviews, documentation, and tests. The results showed that project-based learning effectively fostered character values such as responsibility, cooperation, care, and discipline. Four key indicators of environmental awareness were identified: (1) adherence to classroom cleanliness rules was evident as most students maintained clean work areas; (2) the use of trash bins reflected emerging awareness of waste sorting, though inconsistently applied; (3) efficient use of electricity and ventilation was observed through reliance on natural lighting and airflow; and (4) cleaning tools were used responsibly, particularly by students assigned to cleaning duties. These findings suggest that project-based learning strengthens students’ environmental awareness through hands-on experiences, despite challenges such as inconsistent waste separation habits.